REVISIONISME STUDI AL-QUR`AN DI BARAT: PENDEKATAN, TIPOLOGI, DAN RELASI PENGETAHUAN-KUASA DALAM KAJIAN DAVID S. POWERS TENTANG AYAT-AYAT WARIS - Wardani Wardani (Pascasarjana UIN ANTASARI Banjarmasin, 2020)
The commonly accepted assumption among Muslims is that the Islamic law of inheritance known as ‘ilm al-farā`idh represents what correctly understood from the Qur`ān. This article is intended to study David S. Powers’ study of the transformation of the so-called proto-Islamic law of inheritance accepted from the Prophet into this science. The study will be focused on his approach to this issue, his stand within oriental study of the Qur`ān, and his study viewed from pos-colonial perspective. Employing synthesized typology of orientalists’ stand in studying Islam, and Edward Said’s perspective of the so-called “intellectual powers”, in this article, I argue that Powers’ study of the issue represents revisionist’s stand of Islam and the Qur`an, applying synthesized approaches of literary and historical criticism. But, his analysis belongs the Western radical analysis of influence of Roman law on the Islamic law and in the context of West-East opposision, reflects Western people’s superiority against Eastern’s (Muslim community) inferiority in understanding their own scripture, the Qur`ān.